Fatigue life evaluation of gold wire bonding solder joints in MEMS pressure sensors. (1st February 2023) - Zhang, Yunfan; Wu, Kangkang; Shen, Shengnan; Zhang, Quanyong; Cao, Wan; Liu, Sheng
Abstract: The failure of the gold wire bonding solder joint of a MEMS pressure sensor caused by the thermal cycling test was investigated with thermal cycling experiments and fatigue simulations. The results show that the maximum stress and strain occurred at the root of the solder joint on the substrate. With the accumulation of strain caused by thermal cycles, the bonding area of solder joint became smaller and the shear force of solder joints reduced to 22.3% after 1600 thermal cycles. The solder joints on the substrate failed after 1940 thermal cycles in plastic fatigue simulations and 3.16 × 10 8 thermal cycles in creep fatigue simulations. Plastic fatigue is the major factor for thermal failure of gold wire bonding.